ACNE VULGARIS BERBASIS PATOGENESIS - Centya Cheirini; Hendra Tarigan; Aditya, Muhammad; Kurniawan, Betta (Medula, 2025)
Acne vulgaris is a chronic inflammatory disease characterized by polymorphic lesions in the form of comedones, papules, pustules, nodules & cysts in predilection locations. Acne vulgaris is the third most frequent case of the 10 most common skin diseases that often come to health services. The incidence of acne vulgaris can occur due to various factors, including increased androgen hormones, increased sebum production and excessive growth of the Cutibacterium acne bacteria. Cutibacterium acnes bacteria play a role in the inflammatory process which increases the worsening of skin conditions with the enzymes and pro-inflammatory factors produced. Young people are the age who suffer from acne vulgaris more often (85%) with a range of 12-25 years. The diagnosis of acne vulgaris is generally easy to make but therapy results are often unsatisfactory. Medications that are often involved in treating acne vulgaris are the use of topical and systemic antibiotics, retinoids, and anti-clindamycin agents. The purpose of this review article is to find out more about acne vulgaris based on pathogenesis. It is hoped that a deeper understanding of the pathogenesis of acne vulgaris will be able to provide much better therapeutic options, resulting in optimal improvements in acne vulgaris therapy.